Effects of local nitric oxide release on human mesenchymal stem cell attachment and proliferation on gelatin hydrogel surface. Issue 4 (December 2013) - Xing, Qi; Yates, Keegan; Bailey, Avery; Vogt, Caleb; He, Weilue; Frost, Megan C.; Zhao, Feng
Abstract : Nitric oxide plays important roles in cardiovascular homeostasis, immune responses and wound repair. Therefore, polymers that release nitric oxide locally at the surface exhibit improved biocompatibility for biomedical implants through reducing neointimal hyperplasia and thrombosis caused by blood vessel wall damage. The objective of this article was to fabricate a nitric oxide–releasing gelatin hydrogel that can continuously generate nitric oxide at a physiologically relevant level and inhibit cell attachment and proliferation. The nitric oxide donor, S-nitroso- N -acetylpenicillamine (SNAP), was successfully conjugated to the gelatin hydrogel, which showed a rapid nitric oxide release in the first 2 h and then a slower but sustained release in the next 70-h period. Human mesenchymal stem cells (hMSCs), as a model cell line with wide biomedical applications, were used to examine the cell attachment and proliferation of the nitric oxide–releasing gelatin hydrogel. Compared with the control gelatin, the nitric oxide–releasing gelatin hydrogel demonstrated a 0·35 times lower hMSCs attachment at 6 h and a 3·15 times lower hMSCs proliferation after 72-h incubation. Moreover, hMSCs on nitric oxide–releasing gelatin exhibited a rounder cell shape and covered less cellular area than their counterparts on the control gelatin hydrogel. This gelatin hydrogel with local nitric oxide release at physiological level provides a promising therapeutic approach in enhancing the performance of biomedical implants.